Los tribunales constitucionales y el control del Derecho interno conectado con el comunitario - Alonso García, Ricardo (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
Analysis of the role of national Courts within the European Union, including Constitutional (or Supreme) Courts, before domestic Law implementing Community Law. An effort to avoid, as far as possible, declaring the unconstitutionality of domestic Law, which could entail unnecessary or incoherent declarations of unconstitutionality of Community Law.
Keywords: Constitutional courts; Community Law; Supremacy; Consistent interpretation; Community preliminary ruling; Preliminary ruling on constitutionality; Legal certainty; Action for infringement; Judiciary independence; Effects of judgements declaring unconstitu